The Effect of the KWL Strategy on the Acquisition of Some Basic Basketball Skills by Students - Ahmed Rahim Latif (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
The aim of this study was to investigate the effect of the K.W.L. strategy on cognitive achievement and the learning of some basic basketball skills among secondary school students. The researcher employed an experimental approach using a two-group design (experimental and control groups) with pre- and post-tests. The research population consisted of 120 fourth-year secondary school students at the University Co-educational Secondary School for the academic year 2025–2026. A sample of 40 students was selected at random and divided into two groups of 20 students each. The experimental group adopted the K.W.L. strategy, whilst the control group used the traditional method. The skills tests included: the chest compression test, the defibrillation test, and the first-aid assessment test, with the validity, reliability and objectivity of the tests verified. The main experiment lasted for eight weeks, with one teaching unit per week, incorporating the stages of the (What do I know? What do I want to know? What have I learnt?) within the main section of the lesson. The results showed statistically significant differences between the pre- and post-tests in favour of the post-tests in both groups; however, the improvement was greater in the experimental group. The results also showed that the experimental group outperformed the control group in all the skills under investigation, confirming the effectiveness of the K.W.L. strategy in improving skill learning and cognitive achievement in basketball. The researcher attributes this to the strategy’s role in activating prior knowledge, increasing mental engagement, and enhancing motivation and feedback during learning. The study recommended the need to employ active learning strategies, particularly the K.W.L. strategy, in physical education teaching and to apply them to different sports and educational stages.